2022
DOI: 10.3390/jcm11102864
|View full text |Cite
|
Sign up to set email alerts
|

Caries Experience and Increment in Children Attending Kindergartens with an Early Childhood Caries Preventive Program Compared to Basic Prophylaxis Measures—A Retrospective Cohort Study

Abstract: Dental caries constitutes a public health challenge. As preventive strategies are desirable, this retrospective cohort study aimed to assess the caries experience and increment in children attending kindergartens with an early childhood caries (ECC) preventive program (intervention group, IG) compared to basic prophylaxis measures (control group, CG) located in areas of different socioeconomic status (SES) within Marburg (Germany). The long-term caries experience (2009–2019) of these 3–5-year-old kindergarten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…52 At an individual level, tooth brushing with fluoride toothpaste has shown standalone benefit in reducing caries prevalence, while other strategies, such as the application of fluoride varnish, do not appear effective in isolation to reduce caries progression. 53 A Cochrane systematic review evaluating the impact of tooth brushing showed a 24% reduction in caries experience as measured by DFMS scores among children using fluoridated toothpaste versus those using non-fluoridated toothpaste. 54 Given the lack of data regarding the decrease in progression rates using a multipronged approach, we assumed a 30% reduction based on diverse literature.…”
Section: Discussionmentioning
confidence: 99%
“…52 At an individual level, tooth brushing with fluoride toothpaste has shown standalone benefit in reducing caries prevalence, while other strategies, such as the application of fluoride varnish, do not appear effective in isolation to reduce caries progression. 53 A Cochrane systematic review evaluating the impact of tooth brushing showed a 24% reduction in caries experience as measured by DFMS scores among children using fluoridated toothpaste versus those using non-fluoridated toothpaste. 54 Given the lack of data regarding the decrease in progression rates using a multipronged approach, we assumed a 30% reduction based on diverse literature.…”
Section: Discussionmentioning
confidence: 99%